Simulation as enabling technologies for agile thinking: training and education aids for decision makers. (1st January 2014) - Bruzzone, Agostino G.; Massei, Marina; Tremori, Alberto; Poggi, Simonluca; Nicoletti, Letizia; Baisini, Claudia
This paper describes ongoing researches and preliminary results obtained about the potential of serious games for identification, development and education of specific soft skills. These characteristics correspond to the capability to catch at glance a solid understanding of the details in a scenario or the identification of missing elements in a set of information. This paper proposes an interdisciplinary research where expertise in modelling and simulation and serious gaming are mixed with skills in education and decision-making development. The authors' goal is to develop a methodology and a set of games that could support decision makers to develop intuition and the capability to think and understand out of personal frameworks (Baisini et al., 2010, 2011). Preliminary experimentations are proposed by using an existing serious game 'Sibilla'. The results are also useful to direct the research where to focus the efforts for developing ad hoc games for this very specific purpose.